Manajemen Corporate Social Responsibility GraPari Kota Pekanbaru Dalam Meningkatkan Kepercayaan Masyarakat - Rahmadika, Hary; Riauan, Muhd Ar. Imam (The Journal of Communication Management and Organization, 2022)
Corporate Social Responsibility (CSR) is one of the corporate responsibility programs towards stakeholders and the environment in all aspects of the company's operations. This study aims to determine the activities of the GraPari Smart Officer CSR program in increasing public trust. The method used in this research is a qualitative research method with a descriptive approach. Informants in this study are employees at GraPari Telkomsel Pekanbaru City. The results showed that to increase public trust, social mapping was carried out by involving the community, carrying out programs according to the plan, collaborating with foundations engaged in the same field and deploying assistants in the field and building the company's image.